Analysis of Biases in Corporate Income Tax-CIT - Agossadou, Stanislas T. Médard D. C. (My University, 2023)
This paper analyzes the biases in CIT in some countries around the world. Most corporate tax systems are found in the Tax Codes. The sample covers the Tax Codes in force in ten countries in Africa, America, Asia and Europe. Assuming that corporate tax is the cost of using public capital, the analysis of the content of these tax codes relating to corporate income taxation, has made it possible to identify several biases or differences in taxation and/or tax treatment. The biases in CIT identified relate to financing, investment, result, rate and tax base. This paper is one of the first to expand the literature by analyzing the biases in CIT, likely to affect tax behavior and, by extension, the financial behavior of firms.
Keywords: Corporate income tax; tax difference; tax bias; Tax Code